Analisis Efektivitas Service Excellent terhadap Kepuasan Nasabah di BPR Sentral Arta Jaya KC Kraksaan - Adi Yasin Mualana Azis; Dimas Arfiansah Putra; Muhammad Fadli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the implementation of excellent service and its impact on the level of customer satisfaction at BPR Sentral Arta Jaya KC Kraksaan. The method used is qualitative with a case study design. The subjects of the study included 10 customers who had been loyal customers for more than five years, plus one teller and one customer service (CS). Data was obtained through in-depth interviews, direct observation, and document review, then analyzed using the Miles & Huberman framework that includes data reduction, data presentation, and conclusion drawn. The results showed that the majority of respondents (around 80%) felt very satisfied with the services provided. This is because employees are considered friendly, communicative, able to give clear directions, and foster trust. Meanwhile, a small percentage of customers (20%) expressed satisfaction but submitted notes, especially regarding the inconsistency of field officers in meeting the visit schedule. Interviews with tellers and CS also affirmed the commitment to providing excellent service through friendliness, thoroughness, and the ability to offer solutions to customer problems. In addition, it was found that personal interaction and emotional closeness between officers and customers also affect the perception of satisfaction. The trust built from quality services has an impact on long-term loyalty, which ultimately supports the sustainability of the bank's business. Overall, the excellent service practices at BPR Sentral Arta Jaya KC Kraksaan have proven to be effective in increasing customer satisfaction and loyalty, although the reliability and consistency of service in the field still require attention and continuous evaluation.